MENYIAPKAN ALUMNI MERINTIS WIRAUSAHA KEBIDANAN DENGAN POSTPARTUM MASSAGE AND SPA ENTREPRENUERSHIP: MENGANTAR MIORI MENGGAPAI MIMPI (TAHUN KE III) - Nur Rahmawati, Rahajeng Siti; Rahmaningtyas, Indah; Titisari, Ira (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
To address the discomforts experienced during the postpartum period, when mothers must adapt to their bodies returning to their pre-pregnancy state, along with adjusting to their new roles and the challenges of breastfeeding, several therapies can be undertaken. One such therapy is postpartum and lactation massage. In line with the vision of Kediri Midwifery Study Program Campus IV, which is "To Produce Civilized Midwife Graduates, Excellent in Entrepreneurship, and Globally Competitive," it is meaningful to support alumni who remain dedicated to their profession as well as those who are aspiring to start their own businesses by providing training in Postpartum and Lactation Massage. This training is part of the Tri Dharma of Higher Education, offering guidance to alumni until they can independently run their businesses and even create job opportunities for their peers. This three-day activity was held at the Entrepreneurship Laboratory of Campus IV, Kediri Midwifery Program, Poltekkes Kemenkes Malang. On the first day, participants received materials on the physiology and psychology of postpartum mothers, lactation management, lactation counseling, and simulations of postpartum and lactation massage. The second day focused on Business Management and Digital Promotion, while the third day involved direct simulations of postpartum and lactation massage on postpartum patients. The training was attended by 15 participants. The outcome of this community service activity was an increase in participants' knowledge, as demonstrated by the average pre-test score of 74, which rose to 94 in the post-test. Keywords: Postpartum Massage, Lactation Massage, Digital Promotion, Business Management